Labor Anticommunism in the United States of America and the United Kingdom, 1920–49. (January 2018) - Luff, Jennifer
Why did domestic anticommunism convulse the United States of America during the early Cold War but barely ripple in the United Kingdom? Contemporaries and historians have puzzled over the dramatic difference in domestic politics between the USA and the UK, given the countries' broad alignment on foreign policy toward Communism and the Soviet Union in that era. This article reflects upon the role played by trade unions in the USA and the UK in the development of each country's culture and politics of anticommunism during the interwar years. Trade unions were key sites of Communist organizing, and also of anticommunism, in both the USA and the UK, but their respective labor movements developed distinctively different political approaches to domestic and international communism. Comparing labor anticommunist politics in the interwar years helps explain sharp divergences in the politics of anticommunism in the USA and the UK during the Cold War.